eCM 2014
DOI: 10.22203/ecm.v028a19
|View full text |Cite
|
Sign up to set email alerts
|

Role and regulation of RUNX2 in osteogenesis

Abstract: Runt-related transcription factor 2 (RUNX2) is a transcription factor closely associated with the osteoblast phenotype. While frequently referred to, the complexity of its regulation and its interactions within the osteoblast differentiation pathway are often overlooked. This review aims to summarise the knowledge of its regulation at the transcriptional, translational and post-translational level. In addition, the regulation of RUNX2 by factors commonly used during osteogenic studies will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
386
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(403 citation statements)
references
References 162 publications
11
386
0
6
Order By: Relevance
“…Runx2 plays an essential role in the differentiation of immature osteoblast and is regarded as an early marker of osteoblast. 24 In this study, we found that …”
Section: Protein Expressionmentioning
confidence: 59%
“…Runx2 plays an essential role in the differentiation of immature osteoblast and is regarded as an early marker of osteoblast. 24 In this study, we found that …”
Section: Protein Expressionmentioning
confidence: 59%
“…As can be seen in Figure 7, after a single day of LCN2 exposure, the expression of runt-related transcription factor 2 (RUNX2), a master transcription factor associated with osteoblast differentiation, [20][21][22][23] was significantly increased ( Figure 7A). Similarly, the expression of TGF-b and VEGF transcripts (growth factors known to be important in remodeling the MF microenvironment) [24][25][26] was also increased ( Figure 7B), whereas bone morphogenetic protein 2 (BMP2), a member of the TGF-b superfamily involved in osteoblast differentiation, [25][26][27] was increased on day 1 and day 6 of culture.…”
Section: The Effects Of Lcn2 On Msc Gene Expressionmentioning
confidence: 95%
“…Similarly, the expression of TGF-b and VEGF transcripts (growth factors known to be important in remodeling the MF microenvironment) [24][25][26] was also increased ( Figure 7B), whereas bone morphogenetic protein 2 (BMP2), a member of the TGF-b superfamily involved in osteoblast differentiation, [25][26][27] was increased on day 1 and day 6 of culture. In addition, 2 known products of osteoblasts, osteoprotegerin (OPG) and collagen type 1(COL1A1), 20,21 were also increased after incubation with LCN2 ( Figure 7C). By contrast, incubation with LCN2 markedly decreased PPARg gene expression, which is associated with adipogenesis ( Figure 7D).…”
Section: The Effects Of Lcn2 On Msc Gene Expressionmentioning
confidence: 95%
“…RUNX2 sumoylation, ubiquitination, and acetylation are tightly linked with protein stability (3,14), and acetylated RUNX2 shows increased transactivation activity (14). Phosphorylation is a common protein modification.…”
mentioning
confidence: 99%